Time‐of‐Arrival of Coronal Mass Ejections: A Two‐Phase Kinematics Approach Based on Heliospheric Imaging Observations - Evangelos Paouris; Angelos Vourlidas (Space Weather)
Abstract The forecasting of the Time‐of‐Arrival (ToA) of coronal mass ejections (CMEs) to Earth does not yet meet most Space Weather users' requirements. The main physical reason is our incomplete understanding of CME propagation in the inner heliosphere. Therefore, many ToA forecasting algorithms rely on simple empirical relations to represent the interplanetary propagation phase using, mostly, kinematic information from coronagraphic observations below 30 solar radii (Rs) and a couple rather simplifying assumptions of constant direction and speed for the transient. We replace the assumption of constant speed in the inner heliosphere with a two‐phase behavior consisting of a decelerating (or accelerating) phase from 20 Rs to some distance, followed by a coasting phase to Earth. In a nod toward a forecasting scheme, we consider Earth‐directed CMEs, use kinematic measurements only from the Heliospheric Imagers aboard both STEREO spacecraft, treat each spacecraft separately to increase the event statistics, analyze the measurements in a data‐assimilative fashion, and intercompare them against three localization schemes for single viewpoint observations (fixed‐φ, harmonic mean and self‐similar expansion). For the 21 cases, we obtain the best mean absolute error (MAE) of 6.4 ± 1.9 hr. In fact, the difference between calculated and observed ToA is <52 min for 42% of the cases that return plausible ToA estimates. We find that some CMEs continue to decelerate beyond even 0.7 AU but reasonable forecasts should be possible with 31 hr lead time. This work is a proof‐of‐concept and an analysis of a larger event sample is required to fully validate this technique.